Wage Flexibility and the Great Recession: The Response of the Irish Labour Market - Aedin Doris; Donal O'Neill; Olive Sweetman (Institute for the Study of Labor (IZA), 2013)
There is considerable debate about the role of wage rigidity in explaining unemployment. Despite a large body of empirical work, no consensus has emerged on the extent of wage rigidity. Previous attempts to empirically examine wage rigidity have been hampered by small samples and measurement error. In this paper we examine nominal wage flexibility in Ireland both in the build up to, and during the Great Recession. The Irish case is particularly interesting because it has been one of the countries most affected by the crisis. Our main analysis is based on earnings data for the entire population of workers in Ireland taken from tax returns, which are free of reporting error. We find a substantial degree of downward wage flexibility in the pre-crisis period. We also observe a significant change in wage dynamics since the crisis began; the proportion of workers receiving wage cuts more than doubled and the proportion receiving wage freezes increased substantially. However, there is considerable heterogeneity in wage changes, with a significant proportion of workers continuing to receive pay rises at the same time as other were receiving pay cuts.
Keywords: J31; J38; D31; 330; wage flexibility; Great Recession